Large-eddy simulations on distributed shared memory clusters - Stone, Christopher; Menon, Suresh (Journal of parallel and distributed computing, 2004)
The practicality of Large-eddy simulation (LES) of turbulent combustion, as is found in gas turbine engines, on clusters of commodity PC-based symmetric multi-processor (SMP) systems in 2-, 4-, and 8-way configurations has been investigated. Bandwidth demands from both memory and networking in the benchmark LES algorithm are shown to the primary performance inhibitors. Contention in the various SMP architectures tested is shown to compound these two hardware limitations. To investigate the ability of the parallel clustered systems, low-level hardware studies are conducted in conjunction with bench-marking of the LES application. The hardware tests focus on memory and communication contention under loads found in the LES algorithm. For comparison, the benchmarks are also applied to two industry leading high-performance super-computing architectures. It is found that contention in the 4- and 8-way SMP architecture studied here limits their applicability while the 2-way systems shows competitive performance and speed-up compared to its industry counter-parts. It is concluded that design-level combustion LES on clusters of commodity hardware, when equipped with sufficient memory and communication bandwidth, are a viable substitute for more expensive super-computing platforms.